Alih Kode dan Campur Kode dalam Novel Kambing dan Hujan Karya Mahfud Ikhwan - Septriani, Hilda (Puitika, 2025)
Literary works have an essence as a medium of communication between the author and the reader. Authors write their creative ideas based on their experiences and record the dynamics of the society around them. In general, the author raised some characteristics, both in storytelling techniques and the use of local language as an identity. This study aims to reveal the phenomenon of code-switching and code-mixing in Mahfud Ikhwan's "Kambing dan Hujan" and analyze the ideology behind the language phenomenon. The Indonesian language, the language of unity, is considered less able to be an agency in carrying the local nuances displayed in the novel. Switching and mixing languages in cultural dialogue further shows an ideological process in creating a work. The results show that localized words such as "mindo, wedding, monggo, mbok, rek, cak" and others in the novel are considered more capable and represent the delivery of cultural messages more comprehensively. The local language is retained because if it is replaced with Indonesian, it is considered less able to convey the essence because of the change in meaning. In addition, the phenomenon of code-switching and mixing with local languages can also be a strategy to maintain the cultural meaning of the story.